THE EFFECT OF WORK-LIFE BALANCE AND FLEXIBLE WORKING ARRANGEMENT ON EMPLOYEE PERFORMANCE AND JOB SATISFACTION AT PT. KMK GLOBAL SPORTS - Dewi, Citra Kusuma; Sunaryo, Dede; Galuh, Hendra (Penelitian dan Pengembangan Ilmu, 2025)
This study investigates the influence of work-life balance and flexible working arrangements on employee performance and job satisfaction, with a specific focus on female employees at PT KMK Global Sports. Utilizing a quantitative approach and structural equation modeling, the study explores how modern workplace policies affect key employee outcomes. The findings reveal that both work-life balance and flexible working arrangements have a direct and positive impact on employee performance and job satisfaction. Interestingly, job satisfaction does not mediate the relationship between these two variables and performance, suggesting that the benefits of supportive work policies may translate directly into improved productivity, independent of job satisfaction levels. These insights underscore the importance for organizations to prioritize flexible and balanced work environments as strategic tools to enhance workforce efficiency and well-being.